2019
DOI: 10.1136/bmj.l879
|View full text |Cite
|
Sign up to set email alerts
|

China’s response to the rising stroke burden

Abstract: Zixiao Li and colleagues discuss why the number of strokes is growing in China and how the country is taking steps to reduce the rate and improve care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 28 publications
0
88
0
Order By: Relevance
“…Currently, stroke has become the second leading cause of death next to heart diseases, which killed 5.5 million persons per year (1). According to statistics, the aging of population was one of the major causes of increased incidence of stroke (2).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, stroke has become the second leading cause of death next to heart diseases, which killed 5.5 million persons per year (1). According to statistics, the aging of population was one of the major causes of increased incidence of stroke (2).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the leading cause of death in China (1). China's National Stroke Registry investigated patients who had previously experienced acute ischemic stroke and found that the 1-year recurrence rate of stroke was 17.7% (2).…”
Section: Introductionmentioning
confidence: 99%
“…The rapidly ageing population is one of the major reasons for this high prevalence. (1,2) The location of stroke in the brain has a strong in uence on the clinical consequences. (3) In most cases, stroke occurs only in one hemisphere of the brain and results in impairment on the opposite side of the body.…”
Section: Introductionmentioning
confidence: 99%